Chemo‐Phototherapy with Carfilzomib‐Encapsulated TiN Nanoshells Suppressing Tumor Growth and Lymphatic Metastasis - Wu, Xuan; Wang, Le; Xu, Yan‐Neng; Chen, Jian‐Li; Luo, Kathy Qian; Yuan, Ming‐Heng; Li, Jie; Yuan, Gang; Gu, Ze‐Yun; Jia, Xiao‐Hui; Chen, Xiuping; Zhu, Xiao‐Ming; et al. (Small (Weinheim an der Bergstrasse, Germany), 2022)
The design of nanomedicine for cancer therapy, especially the treatment of tumor metastasis has received great attention. Proteasome inhibition is accepted as a new strategy for cancer therapy. Despite being a big breakthrough in multiple myeloma therapy, carfilzomib (CFZ), a second‐in‐class proteasome inhibitor is still unsatisfactory for solid tumor and metastasis therapy. In this study, hollow titanium nitride (TiN) nanoshells are synthesized as a drug carrier of CFZ. The TiN nanoshells have a high loading capacity of CFZ, and their intrinsic inhibitory effect on autophagy synergistically enhances the activity of CFZ. Due to an excellent photothermal conversion efficiency in the second near‐infrared (NIR‐II) region, TiN nanoshell‐based photothermal therapy further induces a synergistic anticancer effect. In vivo study demonstrates that TiN nanoshells readily drain into the lymph nodes, which are responsible for tumor lymphatic metastasis. The CFZ‐loaded TiN nanoshell‐based chemo‐photothermal therapy combined with surgery offers a remarkable therapeutic outcome in greatly inhibiting further metastatic spread of cancer cells. These findings suggest that TiN nanoshells act as an efficient carrier of CFZ for realizing enhanced outcomes for proteasome inhibitor‐based cancer therapy, and this work also presents a “combined chemo‐phototherapy assisted surgery” strategy, promising for future cancer treatment. Carfilzomib (CFZ), a second‐in‐class proteasome inhibitor, is still unsatisfactory for solid tumor and metastasis therapy. In this work, porous titanium nitride (TiN) nanoshells are first synthesized and used as the carrier of CFZ. TiN nanoshells act as an autophagy inhibitor as well as a photothermal agent, sensitizing the anticancer effect of CFZ.